Unveiling The Hidden Eagle: Acute Parotitis-Induced Eagle Syndrome - Permpalung, Nitipong (Medknow Publications & Media Pvt Ltd, 2014)
CONTEXT: A cervicofacial pain and foreign body sensation in pharynx associated with styloid process elongation is called Eagle syndrome. Typically, this syndrome is provoked by tonsillectomy or trauma. We report the first case of acute parotitis-induced Eagle syndrome. CASE REPORT: A 65-year-old woman presented with right facial pain. CT scan of neck revealed asymmetric enhancement of the right parotid gland compatible with acute parotitis. All inflammation was resolved with antibiotics. However, the patient complained of pain in right mandibular region out of proportion to inflammation. Review CT found to have an asymmetrically long right styloid process measures. The diagnosis of acute parotitis-induced Eagle syndrome was established. CONCLUSION: Physicians should have a high index of suspicion for Eagle syndrome in patients with atypical neck pain and elongated styloid process since another significant manifestation of Eagle syndrome is carotid artery compression leading to recurrent syncope or stroke.